2020
DOI: 10.2478/nispa-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Why some Fail and others Succeed: Explaining the Academic Performance of PA Undergraduate Students

Abstract: AbstractThe current research explores the influence of multiple factors (such as class attendance, previous academic performance, in-class involvement and attention, class schedule, gender and other control variables) on the academic performance of public-administration undergraduate students. The regression models developed based on the academic literature were tested on a sample of 1st-year students (N = 115) enrolled in the Public Administration bachelor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This finding is consistent with that obtained by other recent studies since it has been shown that the persistence and university dropout of university students depends on a combination of individual, institutional, and economic factors, whose effects on the decision to drop out are mediated by the student's ability to successfully integrate into the academic system [1]. In addition, beyond the situation of vulnerability or social exclusion present in university students, other variables have been detected, such as motivation, which plays a key predictive role in the academic achievement of students [7,68,70,73,143], thus preventing dropout or failure and empowering the students to overcome difficulties, even when starting from disadvantaged social situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with that obtained by other recent studies since it has been shown that the persistence and university dropout of university students depends on a combination of individual, institutional, and economic factors, whose effects on the decision to drop out are mediated by the student's ability to successfully integrate into the academic system [1]. In addition, beyond the situation of vulnerability or social exclusion present in university students, other variables have been detected, such as motivation, which plays a key predictive role in the academic achievement of students [7,68,70,73,143], thus preventing dropout or failure and empowering the students to overcome difficulties, even when starting from disadvantaged social situations.…”
Section: Discussionmentioning
confidence: 99%
“…Third, in terms of student motivation, it has been shown that there is a clear relationship between this variable and university dropout cross-culturally, obtaining the same clear positive tie between high motivation and a lower probability of university dropout in different countries and diverse cultural settings [65][66][67][68][69][70][71][72][73]. In fact, a correlation has been found between motivation and positive behavior of students, as well as favorable involvement in the learning process and academic achievement [7,46,[74][75][76][77][78][79][80][81], in such a way that the most motivated students show less disruptive and/or challenging behavior, greater commitment to the learning process, and higher probabilities of achieving academic achievement.…”
Section: Key Variablesmentioning
confidence: 99%
“…Research has been carried out in areas such as psychology, where, apart from demographic data, the influence of variables related to interest, motivation, attendance, integration, self-regulation, commitment, participation, anxiety, and communication on academic performance have been considered (17)(18)(19)(20)(21). From the field of statistics, contributions have been made such as those reflected in (21)(22)(23), which apply statistical models that seek to examine the variables involved in university admission (admission and pre-university exams), proposing a model that involves various interrelated variables in an attempt to predict academic performance. Some early research have grouped the variables into economic, demographic, and psychological factors (24,25).…”
Section: Figure 1 Overview Of Machine Learningmentioning
confidence: 99%
“…The fields or areas of knowledge that have studied the multidimensional variable of academic performance are diverse. This has been approached from the field of psychology (17)(18)(19)(55)(56)(57), which has applied tools related to questionnaires on students' perceptions regarding academic performance, followed mainly by statistical tools that have a much more marked focus on demographic data and their influence on the variable of interest (21,22,58,59). Likewise, research related to data science is important, especially studies that use data mining algorithms and ML applied to the field of education.…”
Section: Contributions and Organizationmentioning
confidence: 99%